Seroprevalence of SARS-CoV-2 antibodies in Bali Province: Indonesia shows underdetection of COVID-19 cases by routine surveillance - Anak A. S. Sawitri; Putu C. D. Yuliyatni; Putu A. S. Astuti; Emita Ajis; Endang B. Prasetyowati; Husni; Juliette Morgan; Jennifer Mika; Catharina Y. Praptiningsih; Amalya Mangiri; Ester Mulyadi; Rintis Noviyanti; et al. (Public Library of Science (PLoS), 2022)
The international tourist destination of Bali reported its first case of Coronavirus Disease 2019 or COVID-19 in March 2020. To better understand the extent of exposure of Bali's 4.3 million inhabitants to the COVID-19 virus, we performed two repeated cross-sectional serosurveys stratified by urban and rural areas. We used a highly specific multiplex assay that detects antibodies to three different viral antigens. We also assessed demographic and social risk factors and history of symptoms. Our results show that the virus was widespread in Bali by late 2020, with 16.73% (95% CI 12.22-21.12) of the population having been infected by that time. We saw no differences in seroprevalence between urban and rural areas, possibly due to extensive population mixing, and similar levels of seroprevalence by gender and among age groups, except for lower seroprevalence in the very young. We observed no difference in seroprevalence between our two closely spaced surveys. Individuals reporting symptoms in the past six months were about twice as likely to be seropositive as those not reporting symptoms. Based upon official statistics for laboratory diagnosed cases for the six months prior to the survey, we estimate that for every reported case an additional 52 cases, at least, were undetected. Our results support the hypothesis that by late 2020 the virus was widespread in Bali, but largely undetected by surveillance.